Peranan Kepolisian dalam Menindak Pelaku Pemerkosaan terhadap Anak Kandung - Maharani Maharani; Enny Ristanti; Nahdiya Shabrina (University of Merdeka Malang, 2021)
The crime of rape is the case that causes the most difficulties in its resolution, both at the stage of investigation, prosecution, and at the stage of making a decision. In this study, the formulation of the problem is